The influence of the general operating environment on the development and change toward the resilience of the foreign ethnic restaurants in Malaysia / Mohd Noor Azmin Akbarruddin - Akbarruddin, Mohd Noor Azmin (2020)
For majority of the developing country, receiving the economics boost in the form of foreign direct investment has been one of the proven and effective measure to directly enhance a country's economic condition. The spillover effect from the economic wellbeing will indirectly affect key performance area in the country such as the political stability, positive business environment and the standard of living. However, despite the positive outlook on the foreign direct investment, there are a lot of challenges faced by the foreign ethnic restaurants that venture into this country. The effect of problems and unexpected crisis faced by the foreign ethnic restaurants are stronger since they are operating in unfamiliar business environment. The differences that existed between the local and foreign food socio-culture has presented the foreign ethnic restaurants with issue in attracting the potential customers. Eventually, those issues and unexpected crisis were detrimental to foreign ethnic restaurants operation in the country especially in term of its resilience. The present study, thus empirically measures the influence of the general operating environment attributes, namely technological factors, economic factors and political-regulatory in tandem with food socio-culture, organization development and change influence toward the foreign ethnic restaurants' resilience. Those attributes (technological factors, economic factors and political-regulatory factors) are anticipated toward certain degree to influence the foreign ethnic restaurant business operation resilience. Additionally, organization development and change as well as food socio-culture are also presumed to respectively display mediating and moderating effect in the study. The research is designed through a mixed methodology involving a self-administered survey and an in-depth interview with foreign ethnic restaurant owners namely Middle Eastern, Japanese, Korean and Western/European. Data collection is undertaken in five states in Peninsular Malaysia. Receiving 230 valid responses, the data was analyzed via a process of multivariate analysis using covariance based structural equation modelling (CB-SEM) utilizing AMOS (Analysis of Moment Structure) software. The result obtained from the analysis indicate that the economic and political-regulatory factors exert the most influence on the foreign ethnic restaurant resilience. This result is supported by the qualitative findings. In addition, the food socio-culture able to moderate the relationship between development and change toward the foreign ethnic restaurant resilience. This indicate that the customers play an important role in the enhancing the foreign ethnic resilience as well as contributing toward its survival. The combination between quantitative and qualitative results are able to produce richer analysis and discussion which carry varying consequences and implication to the academic perspective and practical perspective particularly to the foreign ethnic restaurant business operation. Based on the notion, it is clear that the technological, economics and political-regulatory factors as part of the general operating environment attributes not only prepare the conducive environment for restaurant business operation but also exerting constant pressure in the form of business uncertainty that require ongoing monitoring to ensure the any form of opportunity can be capitalized and any potential of crisis brewing in the background could be sensed earlier and properly mitigated through ample resources and dynamics change in the restaurant business strategy thus enhancing the foreign ethnic restaurant resilience.